2020
DOI: 10.1002/slct.202003348
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Solar Radiation Aided Green Approach for Preparative Scale and Solvent‐Free Synthesis of 3‐Methyl‐4‐(hetero)arylmethylene Isoxazole‐5(4H)‐ones

Abstract: An efficient, clean, and environmentally benign approach for the synthesis of 3-methyl-4-arylmethylene isoxazole-5(4H)-ones has been developed using concentrated solar radiations (CSR). One pot, multicomponent synthesis from aromatic / heteroaromatic aldehydes, ethyl acetoacetate and hydroxylamine hydrochloride leads to title compounds in high yields. Notably the reaction has been carried out in under solvent and catalystfree conditions within a very short time (3 min). Further, the reaction was scaled up to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…According to literature reports, solar radiation contains UV-Visible and infra-red radiations, which are responsible for rapid vibrational movements of bonds leading to molecular collisions and hence product formation in short reaction times. 32 Therefore, sunlight was chosen as the energy source for all other subsequent reactions. Other abundant and widely utilized catalysts such as Zn dust and Zn(OAc) 2 were also tried but no product was obtained (Table 1, entries 5 and 6).…”
Section: Resultsmentioning
confidence: 99%
“…According to literature reports, solar radiation contains UV-Visible and infra-red radiations, which are responsible for rapid vibrational movements of bonds leading to molecular collisions and hence product formation in short reaction times. 32 Therefore, sunlight was chosen as the energy source for all other subsequent reactions. Other abundant and widely utilized catalysts such as Zn dust and Zn(OAc) 2 were also tried but no product was obtained (Table 1, entries 5 and 6).…”
Section: Resultsmentioning
confidence: 99%
“…UV-visible and IR radiation can occur in many thermal and photochemical processes and some previous reports affirm these consequences [54] For the last few years, many distinguished organic reactions such as Diels-alder reaction [55], Paterno-Buchi reaction [56], Hantzsch reaction [57], and Biginelli reaction [58] have been executed by concentrated solar radiation (CSR). Moreover, CSR can promote the synthesis of chalcones [59], pyrazoles [60], benzimidazoles [61], and isoxazole-5(4H)-one [62]. Besides these, CSR is effectively utilized for palladium, iron, and silver nanoparticle synthesis [53,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…The metal-catalyzed alkynes are described as a route to the synthesis of isoxazoles [ 20 ]. Furthermore, other studies reported the use of intensified sun radiation in the production of 3-methyl-4-aryl methylene isoxazole-5(4H)-ones [ 21 ].…”
Section: Introductionmentioning
confidence: 99%